Changing fortunes: Long-termism - G-Zero, artificial intelligence and debt - Stephen S. Poloz (Bank of Canada, 2019)
This paper looks at the implications for monetary policy of the widespread adoption of artificial intelligence and machine learning, which is sometimes called the "fourth industrial revolution". The paper reviews experiences from the previous three industrial revolutions, developing a template of shared characteristics: new technology displaces workers; investor hype linked to the new technology leads to financial excesses; new types of jobs are created; productivity and potential output rise; prices and inflation fall; and real debt burdens increase, which can provoke crises when asset prices crash. The experience of the Federal Reserve during 1995-2006 is particularly instructive. The paper uses the Bank of Canada's main structural model, ToTEM (Terms-of-Trade Economic Model), to replicate that experience and consider options for monetary policy. Under a Taylor rule, monetary policy may allow growth to run as long as inflation remains subdued, easing the burden of adjustment on those workers directly affected by the new technology, while macroprudential policies help check financial excesses. This argues for a family of Taylor rules enhanced by the addition of financial stability considerations.
Keywords: E; E6; E63; F; F02; F1; F15; F5; F53; F6; H; O; O11; O33; 330; Financial stability; International Topics; Monetary policy; Trade integration; Uncertainty and monetary policy